The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3389/fpubh.2023.1129031
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of posttraumatic stress symptoms among Internally Displaced Christian couples in Erbil, Iraq

Abstract: BackgroundResearch about the impact of war and displacement experiences on the mental health of Internally Displaced People (IDPs) has recently grown. However, a limited number of studies focus on minorities. The objective of the present preliminary study was to estimate the prevalence of posttraumatic stress symptoms (PTSSs) among IDPs who live outside camps and belong to the Christian minority in Iraq, and to identify possible predictors.MethodsOverall, 108 internally displaced Christians (54 married couples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…The current review also revealed that an increased frequency of displacement was also found to be significantly associated with PTSD. The finding is consistent with previous studies [ 21 , 23 , 42 , 67 , 68 ]. The number of times an individual had been displaced was positively associated with the risk of PTSD.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The current review also revealed that an increased frequency of displacement was also found to be significantly associated with PTSD. The finding is consistent with previous studies [ 21 , 23 , 42 , 67 , 68 ]. The number of times an individual had been displaced was positively associated with the risk of PTSD.…”
Section: Discussionsupporting
confidence: 94%
“…This review revealed that being injured is significantly associated with the existence of PTSD among IDPs, which is in line with other studies [ 23 , 42 , 67 ]. Experiencing physical injury during displacement can significantly increase an individual’s risk of developing PTSD because of direct trauma and physical pain, psychological impact of injury, impact on daily living and functioning, limited access to healthcare and support, trauma reactivation, and reminders of injury.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There are many possible reasons for why IDPs are at higher risk of developing mental health disorders. Mental illnesses among IDPs can result from multiple, often intersecting factors including direct exposure to the violence and destruction of war like (e.g., physical assault, the destruction of one's home, the disappearance or death of loved ones) and the stressful social and material conditions such as poverty, malnutrition, the destruction of social network or unemployment (Miller and Rasmussen, 2010;Rofo et al, 2023).…”
Section: Idps and Mental Illness Riskmentioning
confidence: 99%